Dive Behavior of Eastern Chukchi Beluga Whales (Delphinapterus leucas), 1998–2008 - Citta, John J.; Suydam, Robert S.; Quakenbush, Lori T.; Frost, Kathryn J.; O'Corry-Crowe, Gregory M. (ARCTIC, 2013)
We provide an exploratory description of the dive behavior of 23 beluga whales of the eastern Chukchi Sea stock, tagged with satellite-linked time and depth recorders at Point Lay, Alaska, between 1998 and 2007. Because of differences in how transmitters were parameterized, we analyzed data from tags deployed from 1998 to 2002 (n = 20 tags) and data from tags deployed in 2007 (n = 3 tags) separately. Using cluster analysis, we found three basic dive types in the 1998–2002 dataset. “Shallow” diving behavior was characterized by dives mostly 50 m in depth. “Intermediate” diving behavior was characterized by having one mode near the surface and a second mode near 250 m. “Deep” diving behavior was characterized by having one mode near the surface and a second mode more than 400 m from the surface. The average number of dives per hour ranged from 5.1 (SD = 2.1) to 9.8 (SD = 2.9) across dive types, with the fewest dives per hour in the deep diving category. In general, duration of dives ranged from 1 to 18 minutes; however, dives up to 21 minutes occurred in the deepest diving category. We found little evidence that dive behavior of the belugas in our sample varied by sex or age. In general, belugas dove more deeply in the eastern Beaufort Sea than in the western Beaufort or Chukchi Seas. The depths to which belugas most commonly dive in Barrow Canyon and along the Beaufort shelf break (200–300 m) correspond to the boundary where colder Pacific water overlies warmer Atlantic water, which is probably where Arctic cod (Boreogadus saida) are most dense. Diving depths within the Arctic Basin suggest that belugas are foraging mostly within the warm layer of Atlantic Water (~200–1000 m). Nous dressons une description exploratoire du comportement de plongée de 23 bélugas du cheptel de l’est de la mer des Tchouktches dotés de marqueurs d’enregistreurs satellitaires de profondeur temporelle à Point Lay, en Alaska, entre 1998 et 2007. En raison des différences de paramétrage des transmetteurs, nous avons analysé séparément ...